Beyond chronological age: exploring how different future time perspective influences the health tourism intention - Caisheng Liao; Huiqing Xiao; Zhao Li; Yuki Todo (BMC Psychology)
Abstract Background The burgeoning field of health tourism has garnered significant attention due to its integration of health and leisure, reflecting a growing consumer demand for wellness-oriented travel experiences. Based on the socioemotional selectivity theory, this study examines the relationship between future time perspective, health awareness, involvement, and health tourism intention. It aims to understand how different dimensions of future time perspective influence the intention to engage in health tourism, beyond the traditional chronological age. Methods A cross-sectional survey was conducted among individuals aged 16 years and above with normal cognitive function. Data was collected through online questionnaires distributed on popular Chinese social media platforms, WeChat and QQ. A total of 536 valid questionnaires were returned, with a validity rate of 91.47%. The study employed the structural equation modeling (SEM) to test the proposed hypotheses. Results The effect of different dimensions of future time perspective on health tourism intention differed. Limited future time perspective (LFTP) positively influenced health tourism intention, while open-ended future time perspective (OFTP) did not have a significant effect on health tourism intention. Involvement and health awareness not only directly influence health tourism intention, but also mediate the relationship between future time perspective (OFTP and LFTP) and health tourism intention respectively. Moreover, there is a significant difference in the effect of LFTP on healthy tourism intention between different age groups. Conclusions The findings highlight the importance of considering subjective time perspectives in understanding health tourism intention. Health tourism companies should focus on strategies that enhance health awareness and consumer involvement to capitalize on the positive effects of health tourism intention. Additionally, the study suggests that marketing efforts should be tailored to address the specific needs and goals of individuals with different future time perspectives, thereby optimizing the appeal of health tourism products. Future research should explore these relationships across diverse populations and contexts to further refine the understanding of health tourism decision-making.